The Effect of Job Satisfaction on Lecturer Work Organizational Commitment in Colleges of Education - Rifyal Ahmad Lughawi (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
The purpose of this study is to investigate the impact of work satisfaction on lecturers' organizational commitment. The study employs quantitative methodologies as well as correlation analysis. The study was carried out at the Babunnajah High School of Education in Banten Province. The overall population consisted of 96 academics who took part in this study. A questionnaire on a five-point scale was employed as the study tool. There are 32 verified job satisfaction questions and 18 organizational commitment items in the measure. The findings revealed that instructors at the Babunnajah Higher Education School had high levels of work satisfaction and organizational commitment. Job happiness has an effect on professor organizational commitment. As a result, the higher the amount of organizational commitment, the higher the level of work satisfaction. According to the research suggestions, efforts should be made to boost professor work satisfaction.